Shoot growth, tuber yield and quality of two potato cultivars as affected by prohexadione-calcium application - De Oliveira, Luan Santos [UNESP]; Fernandes, Adalton Mazetti [UNESP]; Soratto, Rogério Peres [UNESP]; Han, Daniela [UNESP]; da Silva, Rudieli Machado [UNESP] (FapUNIFESP (SciELO), 2021)
This study evaluated the effects of the rates and timings of prohexadione-calcium (prohexadione-Ca) application on shoot growth, tuber yield, and quality of two potato cultivars (Agata and Mondial). An experiment with each cultivar was carried out in a greenhouse using a randomized block design with four replications. Treatments consisted of a control and single or sequential foliar applications of prohexadione-Ca at the rate of 50 or 100 g ha-1 (50 g ha-1 applied once, 50 g ha-1 applied twice, 50 g ha-1 applied three times, 100 g ha-1 applied once, 100 g ha-1 applied twice, and 100 g ha-1 applied three times). Prohexadione-Ca application changed the distribution pattern of tuber size in both cultivars. A rate of 100 g ha-1 prohexadione-Ca was applied three times between the stages of tuber initiation and tuber bulking, making the haulm length of the plants short for a long time. Prohexadione-Ca application did not alter the tuber yield and quality of the cultivar Agata, but 50 g ha-1 applied three times or 100 g ha-1 applied twice increased tuber yield in the cultivar Mondial. Only in the cultivar Mondial, 50 g ha-1 prohexadione-Ca applied three times increase tuber dry matter, starch, and protein contents.
Keywords: haulm length; plant growth retardants; Solanum tuberosum; tuber number; tuber size